Biophotonics South America 2015
DOI: 10.1117/12.2181040
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Raman study of aging process in diabetes mellitus human voluntaries

Abstract: Accumulation of AGEs [Advanced Glycation End -products] occurs slowly during the human aging process. However, its formation is accelerated in the presence of diabetes mellitus. In this paper, we perform a noninvasive analysis of glycation effect on human skin by in vivo confocal Raman spectroscopy. This technique uses a laser of 785 nm as excitation source and, by the inelastic scattering of light, it is possible to obtain information about the biochemical composition of the skin. Our aim in this work was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The redshift observed at 1664 cm −1 for T60 in group II indicates the change in (Amide I) α ‐helical structure . The observed shift and the intensity differences for various bio‐molecules may be due to the conformational changes because of IR radiation.…”
Section: Discussionmentioning
confidence: 92%
“…The redshift observed at 1664 cm −1 for T60 in group II indicates the change in (Amide I) α ‐helical structure . The observed shift and the intensity differences for various bio‐molecules may be due to the conformational changes because of IR radiation.…”
Section: Discussionmentioning
confidence: 92%
“…An inelastic scattering of monochromatic laser photons by matter which lead to energy transfer and molecular vibrations is elucidated by the Raman phenomenon, promoting a molecular fingerprint . Currently, the studies conducted by Pereira et al showed the effect of chronological aging and the glycation process on the human dermis in diabetic patients and, young and old healthy people using confocal Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%